2006
DOI: 10.1186/1477-7800-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Primary adenoid cystic carcinoma of the breast: case report and review of the literature

Abstract: Adenoid cystic carcinoma (ACC) of the breast is a rare neoplasm accounting for 0.1% of all breast carcinomas, and presenting most commonly as a painful breast mass. In contrast to the aggressive nature of ACC at other sites, ACC of the breast has a favorable prognosis, lymph node involvement or distant metastases seldom occur. Treatment is basically of simple mastectomy. Chemotherapy, radiation and hormonal treatment have been infrequently used and evaluated. We report a case of ACC of the breast managed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
2
9
0
1
Order By: Relevance
“…Supporting findings in previous reports [15,17-21,27,29,31,35-38,48,50,52,54-57], the majority of breast-ACC in the SEER Program was ER-negative/PR-negative; however, hormone receptor-positive tumors have also been described in a minority of cases [22,23,25,32,34,42,58]. Although information on HER-2-neu is not available in the SEER Program, other series have uniformly reported HER-2-neu-negative status in breast-ACC [18,20,21,23,31,34,37,38,42,50,52,55,56].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Supporting findings in previous reports [15,17-21,27,29,31,35-38,48,50,52,54-57], the majority of breast-ACC in the SEER Program was ER-negative/PR-negative; however, hormone receptor-positive tumors have also been described in a minority of cases [22,23,25,32,34,42,58]. Although information on HER-2-neu is not available in the SEER Program, other series have uniformly reported HER-2-neu-negative status in breast-ACC [18,20,21,23,31,34,37,38,42,50,52,55,56].…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to what might be expected with ER-negative, PR-negative, HER-2-neu-negative (triple-negative) breast cancers, the majority of cases of breast-ACC in the SEER Program rarely involved regional LN and most were associated with excellent survival. These findings support clinical reports that largely [12,20-25,29,31,32,34-38,41,42,48,50-52,55,56], but not exclusively [21-24,34,42,49], describe absence of LN involvement and excellent survival [22,24,25]. Metastatic breast-ACC has been rarely reported at initial diagnosis [22], and only one case was observed in the SEER Program over a 30-year period.…”
Section: Discussionsupporting
confidence: 90%
“…Generally, they occur in female patients with a median age of 58 to 64 years. Therefore, there are limited guidelines for treatment and diagnosis, and they are based on guidelines used for ACC of the breast in females (1)(2)(3)(4)(5)(6). In the present study, we reported a rare case of ACC of the breast in a 42 year-old man.…”
Section: Introductionmentioning
confidence: 70%
“…ACC is a rare malignancy of exocrine glands defined by the presence of a dual population of cells, and identical tumors can also arise from the breast. The unique characteristics of breast-ACC include a lack of expression of the estrogen receptor (ER), the progesterone receptor (PR), and HER2 and a basal-like phenotype in transcriptomic analysis [ 1 , 4 , 5 ]. However, HR+ breast-ACC has been reported [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%